Analysis of Pulmonary Function in Thymoma Subjects: A 20-Year Retrospective Cohort Study - Ruan, Hongyun; Liu, Bin; Yang, Xinting; Shang, Xuehui; Li, Qi (The Thoracic and Cardiovascular Surgeon, 2022)
Background Thymoma is the most common tumor of the anterior mediastinum. However, the correlation between thymoma stage and pulmonary function was not assessed. Our objective in this study was to describe the pulmonary function in thymoma subjects stratified with different staging systems.Methods A total of 143 subjects with a diagnosis of thymoma who underwent extended thymectomy for thymoma between January 2001 and December 2019 were reviewed retrospectively. All the subjects experienced pulmonary function tests (PFTs) using Master Screen PFT system and total respiratory resistance measurement.Results We evaluated 143 subjects with a diagnosis of thymoma; the significant differences were observed in mean values of vital capacity, inspiratory volume (IC), total lung capacity (TLC), ratio of residual volume to total lung capacity (RV/TLC), forced vital capacity, forced expiratory volume in 1 second, ratio of forced expiratory volume in 1 second to forced vital capacity, peak expiratory flow, peak inspiratory flow, maximum ventilation volume, total airway resistance, and diffusing capacity for carbon monoxide (DLCO) across upper airway obstruction classification. PFTs of subjects with varying Masaoka stages are different. RV and RV/TLC of subjects in stages III and IV were higher than those of normal level, while DLCO of subjects in stage IV was lower than the normal level, and the mean level of IC showed significant difference between stage II and stage III.Discussion The pulmonary function patterns of thymoma subjects significantly correlate with tumor location and size rather than clinical Masaoka stage.
Keywords: surgery; thymoma; pulmonary function tests; upper airway obstruction (UAO); cohort study